The history of crop science and the future of food - Curry, Helen Anne; Nehring, Ryan (New Phytologist Foundation, 2024)
Historical memory is often short, and perhaps nowhere more so than in scientific research. As scientists chase new insights and novel tools, they are rarely rewarded for possessing deep knowledge of their disciplines' past trajectories. Textbook sidebars spotlight singular individuals or celebrated experiments, and institutional accounts highlight founders and funders. Such highlights introduce a tiny—and unrepresentative—fraction of scientific work. Yet, the possibilities and pitfalls of today's research are conditioned by the past.